Assessing Disclosure Quality of Workforce Transformation under ESRS S1: An IRO–PATM Analysis of the Automotive Industry - Finckh, Carmen; Brück, Lukas; Germer, Vanessa; Rupprecht, Max (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
The transformation of the European automotive industry through electrification and digitalisation is reshaping employment structures and skill requirements. Under the Corporate Sustainability Reporting Directive (CSRD) and the ESRS S1 standard (“Own Workforce”), companies are required to disclose workforce-related impacts within standardised sustainability reporting. However, it remains unclear whether these requirements foster substantive transparency or primarily result in formal compliance. This study examines the quality of workforce transformation disclosures by linking materiality diagnosis of impacts, risks and opportunities (IRO) with management operationalisation across policies, actions, targets and metrics (PATM). Based on a qualitative content analysis of sustainability reports from ten major European automotive manufacturers and suppliers, the study analyses whether identified transformation risks are translated into coherent management structures. The results reveal a structural asymmetry: workforce transformation is predominantly framed as a risk issue, while management responses are mainly communicated through operational measures. Formally codified policies and consistent target and metric systems remain weak. Differences between staff reductions and upskilling/reskilling indicate field-specific disclosure logics. Overall, integration between IRO diagnosis and PATM operationalisation remains partial. The study contributes by systematically analysing disclosure architecture and distinguishing between formal compliance and structural management integration.